Stress-dependent deformations of concrete using porous aggregates - Jóhann Albert Harðarson 1974- (2014)
Stress-dependent deformations of concrete may induce excessive deflections at service loads, which can compromise the performance of a structure. Elastic shortening and the combined effects of creep and shrinkage strains of concrete also cause loss of prestress force applied to prestressed concrete member. The knowledge of locally obtained materials, used in concrete manufacture, is necessary to effectively model structure’s behaviour. Porous basalt rock is the primary source of concrete aggregates in Iceland. Design codes and mathematical models are based on experiments and experience using specific raw materials, not necessarily applying globally. It is therefore essential to validate codes and models to assess their applicability. This thesis is intended to contribute to better understanding of material properties using Icelandic raw minerals. The focus of the thesis is on the mechanical properties, elastic modulus and creep, and includes: An experiment, using several concrete mixes made from different combination of porous and non-porous aggregates. The elastic modulus was measured and compared with literature and design codes. Numerical evaluations for experimental concrete creep data, made of porous and non-porous aggregates, were carried out, as well as a case study, comparing deflection calculations and prestress losses, using valid codes and calculations based on experimental data. The results indicate substantial discrepancies in measured elastic modulus for concrete made from limestone aggregates, compared to estimates based on mean concrete cylinder strength according to Eurocode 2 (EC2). A fairly good correlation can be seen between aggregate porosity and elastic modulus of concrete when using basalt aggregate. Experimental results show that the elastic modulus drops well below the EC2 values, using correction factors from Icelandic National Annex to EC2, if the porosity is excessive. Concrete containing porous basalt aggregate shows greater creep than concrete with granite aggregate. Concrete ...